Insights From a Clinically Orientated Workshop on Health Care Cybersecurity and Medical Technology: Observational Study and Thematic Analysis - Isabel Straw; Irina Brass; Andrew Mkwashi; Inika Charles; Amelie Soares; Caroline Steer (JMIR Publications, 2024)
BackgroundHealth care professionals receive little training on the digital technologies that their patients rely on. Consequently, practitioners may face significant barriers when providing care to patients experiencing digitally mediated harms (eg, medical device failures and cybersecurity exploits). Here, we explore the impact of technological failures in clinical terms. ObjectiveOur study explored the key challenges faced by frontline health care workers during digital events, identified gaps in clinical training and guidance, and proposes a set of recommendations for improving digital clinical practice. MethodsA qualitative study involving a 1-day workshop of 52 participants, internationally attended, with multistakeholder participation. Participants engaged in table-top exercises and group discussions focused on medical scenarios complicated by technology (eg, malfunctioning ventilators and malicious hacks on health care apps). Extensive notes from 5 scribes were retrospectively analyzed and a thematic analysis was performed to extract and synthesize data. ResultsClinicians reported novel forms of harm related to technology (eg, geofencing in domestic violence and errors related to interconnected fetal monitoring systems) and barriers impeding adverse event reporting (eg, time constraints and postmortem device disposal). Challenges to providing effective patient care included a lack of clinical suspicion of device failures, unfamiliarity with equipment, and an absence of digitally tailored clinical protocols. Participants agreed that cyberattacks should be classified as major incidents, with the repurposing of existing crisis resources. Treatment of patients was determined by the role technology played in clinical management, such that those reliant on potentially compromised laboratory or radiological facilities were prioritized. ConclusionsHere, we have framed digital events through a clinical lens, described in terms of their end-point impact on the patient. In doing so, we have developed a series of recommendations for ensuring responses to digital events are tailored to clinical needs and center patient care.